Improve the role of social media marketing in banking sector – the case study of BIDV = Nâng cao vai trò của marketing mạng xã hội trong lĩnh vực ngân hàng. Nghiên cứu cụ thể tại BIDV - Lê, Thúy Ngân (2020)
As we knew, nowadays, Social Media Marketing is widely used by businesses. It is considered as a weapon that can be used largely for free and very easily, in comparison with other promotional tools (Levinson, J.C. & Gibson, S., 2010). The main purposes of using Social Media Marketing are the amplification of word-of-mouth marketing, market research, general marketing, idea generation and new product development, co-innovation, customer service, public relations, employee communications and reputation management. Indeed, social networks can increase product and brand awareness, web traffic, customer loyalty, but also improve the company‟s Search Engine Optimization, and even increase the success of new product launches. According to Hubspot (2012), 57% of SMBs say social media is beneficial to their business. Thus, this research shows the overall knowledge about the social media marketing and some common tools or channel used the most.The second thing this research focuses on the reality of using social media tool in banking sector in Viet Nam. The specific case study in BIDV.The last thing is the solutions suggested to improve the role of social media marketing in BIDV